An in vitro analysis of antiproliferative and antimicrobial activities of solvent fractions of Taraxacum officinale (Dandelion) leaf - C.O. Tettey & , A. Ocloo, P.C.N. Nagajyothi, and K.D. Lee (Journal of Applied Pharmaceutical Science, 2014)
The persistent upsurge in multidrug resistance of common pathogens and global increase in the incidence of non-infectious diseases such as cancers and diabetes has led to an urgent need for the discovery of novel and affordable pharmaceuticals. Taraxacum officinale commonly called dandelion has been used in traditional medicine for the treatment of various conditions. Although the antimicrobial and antiproliferative properties of various crude extracts of T. officinale have been reported, there is little report on the antimicrobial and antiproliferative activities of its solvent fractions. In this study, various solvent fractions from the crude methanolic extract of T. officinale leaves were examined for their antiproliferative and antimicrobial activities with the aim of providing a baseline data for the discovery of the antiproliferative and antimicrobial phytocompounds in T. officinale leaves. Whereas, methylene chloride fraction showed the highest antiproferative activity, inhibiting 97 % proliferation of SGT oral cancer cells the butanol fraction showed the highest antimicrobial activity in both disc diffusion and broth dilution assays. Therefore the methylene chloride and the butanolic fractions could respectively act as leads for the discovery of important anticancer and antimicrobial phytocompounds from T. officinale.
Keywords: Antiproliferative, antimicrobial, solvent fractions, Taraxacum officinale leaf extract.